Structural framework and evolution of the Golfo San Jorge Basin: a synthesis - José Oscar Allard; Nicolás Foix; José M. Paredes; Raúl E. Giacosa; Sebastián A. Bueti; Francisco E. Oporto Romero; Agustín R. Rodríguez (Latin American Journal of Sedimentology and Basin Analysis)
The Golfo San Jorge Basin evolved through a complex multiphase structural history from the Middle Jurassic to the Neogene. Its stratigraphic record captures key tectonic events in central extra-Andean Patagonia during Gondwana fragmentation and the Andes construction, allowing us to refine and calibrate multiscale structural processes associated with extension and positive tectonic inversion. The structural architecture reflects the interplay of upper-crustal remote stress, active basement structures, coaxial and non-coaxial extensional reactivations, short-wavelength tectonic inversion, thermal subsidence, and mantle processes. A comprehensive understanding of these interactions is crucial for improving regional basin models with broader implications for tectonic and petroleum system studies.